ARCHITECTURAL AND METHODOLOGICAL FOUNDATIONS FOR THE DEVELOPMENT OF MODERN EDUCATIONAL BUILDING TYPOLOGIES - Olimjon Abdurakhmonov (Bright Mind Publishing, 2025)
This article analyzes architectural and methodological approaches to improving the typology of modern educational buildings. The research examined the functional, ecological, and technological aspects of educational facilities in Uzbekistan and other countries, and developed new typological models based on advanced international practices. The study proposes design solutions aligned with modern standards using BIM, GIS, and 3D modeling technologies. Additionally, project proposals are presented based on contemporary architectural principles such as environmental sustainability, inclusivity, energy efficiency, adaptive architecture, and user-centered design. The findings are enriched with scientific and practical recommendations to ensure the sustainable and innovative development of educational infrastructure adapted to local conditions.
Keywords: Educational buildings, typology, modern architecture, adaptability, ecological design, BIM, GIS, Uzbekistan.